Maternal and fetal factors associated with non detection of fetal growth restriction at term: a retrospective study - Aziz, Atiya; Tiwari, Shyamji; Dey, Madhusudan; Singh, Suneeta (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2020)
Background: Fetal growth restriction (FGR) is one of the major factors of perinatal morbidity and mortality. Aim was to study the maternal and fetal risk factors associated with non- detection of fetal growth restriction. Methods: A retrospective analysis was done at a tertiary care hospital. 280 term newborn cases weighing <2.5 kg were selected and they were divided into two groups, Group I- FGR detected cases by ultrasound, and group II- FGR non detected cases. Data was collected from the labour room registers. Results: Incidence of FGR found to be 6.8%.The maternal biological factors found to be significantly associated with fetal growth restriction were gestational hypertension, chronic hypertension and anemia. Fewer ANC visits was associated with non-detection of FGR cases. Detection of FGR cases were more if the birth weight found to be <2 kg when compared to non detection of FGR cases. Conclusions: Anaemia and fewer ante natal visits were associated with non detection of FGR at term when compared with antenatally detected FGR patients.